2019
DOI: 10.2298/abs181001054e
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical responses of young olive trees (Olea europaea L.) to water stress during flowering

Abstract: This study examines physiological and biochemical changes in three Moroccan varieties of young olive trees (Olea europaea L.) grown under three different water regimes (control, moderate stress and severe stress). Leaf relative water content (RWC), water potential (Ψw), transpiration rate (E), stomatal conductance (gs), maximum quantum efficiency of PSII (Fv/Fm), the contents of total chlorophyll (TCC), proline (ProC) and soluble sugars (SSC) were measured at the flowering stage during three growing seasons (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Among them, RWC exhibited a negative relationship with proline, which was consistent with the results of Abboud et al [59]. This may relate to an adaptive mechanism to reduce water loss and preserve cell membrane integrity [82].…”
Section: Pcassupporting
confidence: 89%
“…Among them, RWC exhibited a negative relationship with proline, which was consistent with the results of Abboud et al [59]. This may relate to an adaptive mechanism to reduce water loss and preserve cell membrane integrity [82].…”
Section: Pcassupporting
confidence: 89%
“…Under rising water shortages, plant species lose water mainly by transpiration and then they tend to control their stomatal closure. In addition, many studies showed that stomatal closure is a genotypic depending component ( Hajiboland et al ., 2015 ; Ahmad et al ., 2018 ; El et al ., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…PCA is a multivariate statistical analysis used with an emphasis on the reduction of variables that most explain data variability [45][46][47][48][49][50][51][52][53][54][55]. Indeed, several reports used the PCA approach in order to discriminate among cultivars, growing seasons, and growing areas based on physical fruit traits [12,22,56,57].…”
Section: Discussionmentioning
confidence: 99%